2021
DOI: 10.1007/s11557-021-01714-8
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of endophytes from needles, their inoculation with Lophodermium piceae and persistence of this fungus in needles of Norway spruce

Abstract: Lophodermium piceae is the most common endophyte of Norway spruce (Picea abies) needles, and it probably occurs in the total distribution area of Norway spruce. Its significance to the host tree is still largely unknown mainly because no methodology is known for generating endophyte-free saplings nor for inoculation of intact needles with this fungus. We report here how a daily heat treatment at 40 °C for 8 h eradicates endophytes of Norway spruce needles within a few days without causing visible harm to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Eighteen Norway spruce saplings, six of each of three clones (T4658, T4748 and T5134 derived from rooted cuttings and generated at Luke from trees in Central Finland in 2006) were heat treated for eradication of needle endophytes (Müller and Hamberg 2021). Then the saplings were transplanted to a shady garden site outdoors in Helsinki in October 2008 in groups of three seedlings per group including one sapling of each clone.…”
Section: Spruce Saplingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eighteen Norway spruce saplings, six of each of three clones (T4658, T4748 and T5134 derived from rooted cuttings and generated at Luke from trees in Central Finland in 2006) were heat treated for eradication of needle endophytes (Müller and Hamberg 2021). Then the saplings were transplanted to a shady garden site outdoors in Helsinki in October 2008 in groups of three seedlings per group including one sapling of each clone.…”
Section: Spruce Saplingsmentioning
confidence: 99%
“…Thereafter half of the sapling groups were inoculated with L. piceae and the rest were used as controls. Inoculation was achieved by placing naturally shed, highly infected needles on a metal sieve (mesh size 5 mm) that was suspended above each group of three saplings (Müller and Hamberg 2021).…”
Section: Spruce Saplingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Horner et al (2019) found soil should be heated to 50°C for 72 h, while plants could be treated at 40°C for 1-2 days or 35°C for 7 or more days to deactivate P. agathidicida. Furthermore, repeated daily heat treatment of 40°C for 8 h eradicated culturable foliar endophytes of Norway spruce (Picea abies) after 9 days of treatment (Müller and Hamberg, 2021). Lesions on live Citrus paradisi trees were heat treated with a blowtorch resulting in complete mortality of P. parasitica above 60°C with full recovery of the tree (Hough et al, 1979).…”
Section: Introductionmentioning
confidence: 99%